(untitled) (Indonesian Journal of Cultural and Community Development, 2024)
Education is a critical determinant of successful development across economic, social, and cultural dimensions. In parallel, entrepreneurship plays a significant role in regional advancement, particularly within Micro, Small, and Medium Enterprises (MSMEs). Despite the nutritional benefits of Moringa leaves, there is limited awareness among MSME actors regarding their potential applications in health-focused products. This community service program aims to enhance the competencies of MSME entrepreneurs in Ketimang Village by promoting Moringa leaves as a health-beneficial tea. Implementation involved a series of activities, including a location survey, problem formulation, execution, and monitoring, culminating in the development of a community service journal. The outreach efforts led to a marked increase in public awareness about the health benefits of Moringa leaves, particularly in tea form. This initiative uniquely combines educational elements with practical processing methods for Moringa leaves, fostering innovation among local entrepreneurs. The findings underscore the potential of Moringa leaves as a valuable resource for health promotion and entrepreneurial development, suggesting that similar programs could further empower MSMEs while enhancing community health awareness. Highlights: • Increased awareness of Moringa leaves’ health benefits among MSME entrepreneurs. • Utilized a systematic implementation approach, including surveys and evaluations. • Fostered innovation by providing practical methods for processing Moringa into tea. Keywords: Moringa leaves, health benefits, MSMEs, community service, entrepreneurship